Utilization of Village Funds Based on Good Governance as a Formulation of Community Welfare - Dito Aditia Darma Nasution; Iskandar Muda; Mika Debora Br Barus (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
One of the most crucial sources of funding for villages to enhance communal welfare is village finance. This study aims to examine the good governance in the use of village money in the North Tapanuli Regency.  Methods of gathering data include documentation, interviews, and observation in each of the 241 villages that make up the North Tapanuli Regency. In the meantime, the data's veracity is confirmed using the triangulation method. Data reduction, data visualization, and conclusion drawing/verification are all used in data analysis. As demonstrated by community involvement, accountability, responsiveness, and transparency in the use of village funds, the study's findings show that North Tapanuli Regency's good governance-based policy for using village funds as a formulation of community welfare is fairly good. The presence of training programs, productive meetings between facilitators and the government, and coordination among village facilitators to ensure that the rules to be implemented are not obstructed are the elements that strengthen the use of village funds based on good governance. The existence of shifting regulations after the village authority has established the APBDes is the weak point.